Legal and policy provisions for reasonable accommodation in employment of persons with mental disability in East Africa: A review. (May 2019) - Ebuenyi, Ikenna D.; Regeer, Barbara J.; Nthenge, Mirriam; Nardodkar, Renuka; Waltz, Mitzi; Bunders-Aelen, Joske F.G.
Abstract: Despite an elaborated framework on reasonable accommodations in the UN Convention on the Rights of Persons with Disabilities (UN CRPD), persons with mental disabilities continue to face significant limitations to employment in East Africa. The aim of our study is to explore legal provisions related to reasonable accommodations in the employment-related laws regarding persons with mental disabilities in East Africa, and to suggest ways to bridge the gap between principles of international law and provisions of domestic laws. The disability, labour and human rights laws of 18 East African countries were accessed from the database of WHO MiNDbank and the International Labour Organisation. These laws were reviewed in the light of the framework of Article 27 of the UN CRPD. We found that 15 (83%) of the countries in East Africa have ratified the UN CRPD, and 12 (67%) have formulated an explicit definition of disability that includes mental illness. Eleven countries (61%) have explicit laws mandating employers to provide reasonable accommodations for persons with a mental disability. Eight countries (44%) have submitted a state report to the CRPD Committee. Lack of clear and specific definition of reasonable accommodations or the existence of vague definitions create challenges. If persons with a mental disability are to exercise their right to inclusive and gainful employment, there is a need for legal reforms that guarantee access to inclusive employment practices.